2020
DOI: 10.3389/fphar.2020.00019
|View full text |Cite
|
Sign up to set email alerts
|

The Application of DVDMS as a Sensitizing Agent for Sono-/Photo-Therapy

Abstract: Both photodynamic therapy (PDT) and sonodynamic therapy (SDT) are fast growing activated therapies by using light or ultrasound to initiate catalytic reaction of sensitizing agents, showing great potentials in clinics because of high safety and noninvasiveness. Sensitizers are critical components in PDT and SDT. Sinoporphyrin sodium (DVDMS) is an effective constituent derived from Photofrin that has been approved by FDA. This review is based on previous articles that explore the applications of DVDMS mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 80 publications
0
26
0
Order By: Relevance
“…This extremely high extinction coefficient probably results in the high singlet oxygen generation efficiency of DVDMS. Apart from being an effective photosensitizer, DVDMS is also sono-responsive to induce cytotoxicity upon exposure to an acoustic field [21]. DVDMS was found to preferentially accumulate in sarcoma 180 solid tumors and could be locally activated by ultrasound to non-invasively elicit a strong cytotoxic effect without causing any damage to adjacent tissues [16].…”
mentioning
confidence: 99%
“…This extremely high extinction coefficient probably results in the high singlet oxygen generation efficiency of DVDMS. Apart from being an effective photosensitizer, DVDMS is also sono-responsive to induce cytotoxicity upon exposure to an acoustic field [21]. DVDMS was found to preferentially accumulate in sarcoma 180 solid tumors and could be locally activated by ultrasound to non-invasively elicit a strong cytotoxic effect without causing any damage to adjacent tissues [16].…”
mentioning
confidence: 99%
“…Syno-porphyrin sodium (DVDMS) is a hematoporphyrin derivative based on Photofrin; compared to the latter, its high solubility in water determines short-term skin persistence. Different studies showed a greater sensitivity of DVDMS to both light and ultrasound irradiation, with excellent production of singlet oxygen, making it suitable for therapeutic application in different types of cancer, including glioma [ 89 , 90 , 91 , 92 ]. After administration, DVDMS preferentially localizes inside tumor cells mitochondria, probably due to misregulation of BBB patency.…”
Section: Sonosensitizers For Brain Tumorsmentioning
confidence: 99%
“…Available evidences suggest that the potential mechanisms of DVDMS mediated PDT and SDT mainly involving in ROS and apoptosis signaling pathways, the role of autophagy in the process were revealed recently; however, many more potential mechanisms such as regulation of different signaling pathways and the effect on cell pyroptosis and necrocytosis have not been discovered. Besides, advances in the materials and methods of drug delivery may bring opportunities for the application of DVDMS, and the combination of multiple therapeutic strategies (such as SPDT and PACT) may also provide more possibilities [61].…”
Section: Conclusion and Prospectsmentioning
confidence: 99%